High resolution dynamic ocean topography in the Southern Ocean from GOCE - Albertella, Alberta; Savchenko, Roman; Janjic Pfander, Tijana; Rummel, Reiner; Bosch, Wolfgang; Schröter, Jens (Geophysical Journal International, 2012)
A mean dynamic ocean topography (MDT) has been computed using a high resolution GOCE (Gravity field and steady-state Ocean Circulation Explorer) gravity model and a new mean sea surface obtained from a combination of satellite altimetry covering the period 1992 October till 2010 April. The considered gravity model is GO-CONS-GCF-2-TIM-R3, which computes geoid using 12 months of GOCE gravity field data. The GOCE gravity data allow for more detailed and accurate estimates of MDT. This is illustrated in the Southern Ocean where the commission error is reduced from 20 to 5cm compared to the MDT computed using the GRACE gravity field model ITG-Grace2010. As a result of the more detailed and accurate MDT, the calculation of geostrophic velocities from the MDT is now possible with higher accuracy and spatial resolution, and the error estimate is about 7 cms−1 for the Southern Ocean.